Pedagogical conditions of motivational readiness of students to study during a second higher education (for example, English language) - Буренко, Валентина (Educological discourse, 2013)
The article is devoted to the problem of in-service retraining of teachers. The problem of adult education is examined. The author defines the pedagogical conditions of students’ motive acceptance of studying while getting the second higher education (subject: English), the group techniques for developing students communicative skills in the educational process and creating favourable conditions for retraining.